Portofolio Saham Optimal dengan model Markowitz pada saham Perbankan yang terdaftar di LQ 45 tahun 2023 - Riski, Tri Rachmat; Sulistianingsih, Henny (CV. ITTC INDONESIA, 2024)
Investment behavior is the investor's ability to process data and information related to future risk uncertainty. An investor's ability to respond to risk uncertainty is greatly influenced by the investor's knowledge and understanding of the sector being managed. Knowledge supported by a measurement model is expected to be able to provide maximum returns on managed assets. This research aims to find out the optimal shares to invest in. This research is also expected to be able to contribute in providing information and practical approaches for investors when deciding to invest in the capital market. The object of this research is banking companies that are on the LQ 45 index in 2023. The total research sample is 7 companies. The type of data used in this research is secondary data (share prices) and the data analysis technique used is the Markowitz method to obtain an optimal portfolio for investors. The research results show that for investors with the highest risk preferences the recommended allocation of funds to invest is starting with Bank Mandiri, Bank BRI, Bank Syariah Indonesia and Bank BNI with an expected return rate of 4.58 percent and a risk of 0.51 percent, while investors with a risk preference The lowest recommended allocation of funds for investment is starting with Bank BCA, Bank BTN, Bank BNI and Bank Jago with an expected rate of return of 1.24 percent and a risk of 0.011 percent.